(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The notion of control is fundamental for understanding nature and human- made systems, and because of the control on things is a system field, to have a full estimation of control, it is necessary to take a full idea and knowledge on both theory and applications. By using LabVIEW as the motor controller, we can control a DC motor for multiple purposes using only one software environment. I used a simple programming Language Program named Lab-View for that purpose, My objective in this research is to expand an Automatic tuning way for the traditional PID controllers using Lab-View program. the result shows that the use of Lab-View program for real-time monitoring of a motor’s encoder response, saved money because the software acted as a substitute for an oscilloscope. The real time response increased the efficiency of program testing andediting.